Progress in Research on the Role of the Thioredoxin System in Chemical Nerve Injury - Xinwei Xu; Lan Zhang; Yuyun He; Cong Qi; Fang Li (Toxics, 2024)
(1) Background: Various factors, such as oxidative stress, mitochondrial dysfunction, tumors, inflammation, trauma, immune disorders, and neuronal toxicity, can cause nerve damage. Chemical nerve injury, which results from exposure to toxic chemicals, has garnered increasing research attention. The thioredoxin (Trx) system, comprising Trx, Trx reductase, nicotinamide adenine dinucleotide phosphate, and Trx-interacting protein (TXNIP; endogenous Trx inhibitor), helps maintain redox homeostasis in the central nervous system. The dysregulation of this system can cause dementia, cognitive impairment, nerve conduction disorders, movement disorders, and other neurological disorders. Thus, maintaining Trx system homeostasis is crucial for preventing or treating nerve damage. (2) Objective: In this review study, we explored factors influencing the homeostasis of the Trx system and the involvement of its homeostatic imbalance in chemical nerve injury. In addition, we investigated the therapeutic potential of the Trx system-targeting active substances against chemical nerve injury. (3) Conclusions: Chemicals such as morphine, metals, and methylglyoxal interfere with the activity of TXNIP, Trx, and Trx reductase, disrupting Trx system homeostasis by affecting the phosphatidylinositol-3-kinase/protein kinase B, extracellular signal-regulated kinase, and apoptotic signaling-regulated kinase 1/p38 mitogen-activated protein kinase pathways, thereby leading to neurological disorders. Active substances such as resveratrol and lysergic acid sulfide mitigate the symptoms of chemical nerve injury by regulating the Ras/Raf1/extracellular signal-regulated kinase pathway and the miR-146a-5p/TXNIP axis. This study may guide the development of Trx-targeting modulators for treating neurological disorders and chemical nerve injuries.